2005
DOI: 10.1007/s00467-005-2031-5
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin blockade in children with chronic glomerulonephritis and heavy proteinuria

Abstract: Patients with chronic proteinuric nephropathies are at high risk of developing progressive renal insufficiency. There are limited controlled data on the efficacy of potentially toxic immunosuppressive therapies for many of these diseases such as immunoglobulin A nephropathy and idiopathic membranoproliferative glomerulonephritis. This limitation has not deterred healthcare providers from using such agents based on anecdotal experience. We report our experience taking care of three children with heavy proteinur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Although these drugs have proven benefits in some glomerular disorders, they are fraught with significant toxicity. In recent years, efforts have been directed towards alternative and diseasespecific therapies [9][10]12]. Our observations in children treated with angiotensin blockade alone suggest that this may provide an effective alternative to aggressive steroid and immune modulating therapies in some glomerular diseases.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although these drugs have proven benefits in some glomerular disorders, they are fraught with significant toxicity. In recent years, efforts have been directed towards alternative and diseasespecific therapies [9][10]12]. Our observations in children treated with angiotensin blockade alone suggest that this may provide an effective alternative to aggressive steroid and immune modulating therapies in some glomerular diseases.…”
Section: Discussionmentioning
confidence: 95%
“…There are scant anecdotal reports in the literature about treatment of chronic glomerulonephritis with angiotensin blockade in children with normal renal function [10]. Most studies involve patients who are on concurrent immunosuppressive treatment, or have hypertension and renal insufficiency [9,11,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several interventional trials in adults have shown that dual blockade of the RAAS with ACEI and ARB possesses greater antiproteinuric and renoprotective effects than single blockade with an ACEI even at high doses [7][8]19] . However, in children, only few studies have investigated the efficacy of dual blockade of the RAAS on proteinuria, renal function, BP or cardiac structure with ACEI and ARB [9][10][11][12] . Butani [9] has reported on 3 children with chronic glomerulonephritis treated with a combination of ARB and ACEI without concomitant immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…In children, there are only few studies investigating the efficacy of dual blockade of the RAAS with ACEI and ARB [9][10][11][12] . Therefore, the aim of our study was to investigate whether adding an ARB to proteinuric children already under ACEI treatment may further reduce proteinuria.…”
Section: Introductionmentioning
confidence: 99%